The Efficiency of Using Google Classroom to Teach Writing Descriptive Text - kurnia saputri; Eko Kuntarto; Sofyan; Darmawan Budiyanto (UNIB Press, 2023)
The purpose of this study was to determine the effectiveness of Google Classroom, which was used to teach students how to write descriptive text for Junior High School. A quasi-experimental research design used in this study. The participants in this study were students in the eighth grade at SMPN 13 in Palembang. Purposive sampling used to select 60 students for this study. The researchers used a pre-test and post-test method to collect data. The researchers used SPSS to analyze the data and test the hypothesis. When the value of significance (2-tailed) in this study was lower than the significance level (0.000 < 0.05), the Ha was accepted. It means that using Google Classroom had a significant impact on students' achievement in writing descriptive text. However, it can be concluded that Google Classroom significantly enhances the efficiency of teaching students to write descriptive text and assists them in completing and collecting assignments without regard to time or space constraints.